THE DECISIVE ROLE OF INNOVATION IN ECONOMIC DEVELOPMENT - Alisher Mirkholdorov (Modern American Journals, 2025)
Innovation serves as a catalyst for economic growth, efficiency, competitiveness, and sustainable development in today’s knowledge-based economies. This paper examines the transformative power of innovation in shaping economic trajectories, fostering entrepreneurship, and enhancing societal well-being. Exploring the multifaceted impact of innovation on economic development, this paper explores how creativity, technology, and entrepreneurship can enhance prosperity and sustainability in a rapidly changing global landscape.